The Impact of Leadership, Organizational Culture, And Organizational Structure on the Performance of the Finance Department at Aruna Senggigi Hotel - Lalu Imam Hardiansyah; Lalu Takdir Jumaidi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Tourism is a vital economic sector, especially in destinations like Lombok, Known for its halal and sustainable tourism. Aruna Senggigi Hotel, one of the hotels implementing this concept, faces challenges in maintaining financial management efficiency. This study analyses the influence of leadership, organizational culture, and organizational structure on the performance of the finance department at Aruna Senggigi Hotel. The research employs a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis. The results indicate that organizational culture and organizational structure have a significant impact on financial performance, while leadership has no direct effect. These findings confirm that strengthening organizational culture and optimizing organizational structure are key factors in improving the efficiency and financial stability of the hotel.